Spatial networks of electrotechnical wholesalers in the Netherlands: A GIS application - Charlotje Riemers (European Regional Science Association (ERSA), 1998)
The electrotechnical wholesale businesses stimulate the flows of electrotechnical goods, such as materials for electric installation, cables, wire, switchcupboards, audio and video, lights etcetera, from the producers towards the final consumer. They have an intermediate position in the production column between the producers of electrotechnical goods and, among others, the retailers, electricians, building industry. To give this abstract concept of the 'production column' a concrete and spatial interpretation, we set out an inquiry among approximately fifty electrotechnical wholesalers in the Netherlands. This inquiry gave us more insight in the way these wholesalers operate. An important part of the inquiry consisted of questions about the locations of the suppliers and buyers. With postal codes and the use of GIS we were able to show the spatial network of the forward and backward linkages of this particular group of wholesalers. Also other topics, such as the mean distances towards the buyers, have been calculated. In this way we turned the economic concept of the organisation of the production column into a spatial concept of location and spread of the different links in the production column. The paper will consist of two parts. Firstly, an outline will be given of the organisation of the electrotechnical wholesale business. Secondly, the paper will content the recent location pattern of this type of wholesale businesses and the spatial network of the production column of electrotechnical goods.
Keywords: 330